The behavior and ethics of Prince Abdelkader Algerian and his army in the war: "Treatment of prisoners French of war - abdelkader, el meylek (Journal of Social Sciences and Humanities, 2019)
We hope that this scientific paper - God willing - will be amplified by Al-Badi, and is encouraged by Al-Shadi. This paper will attempt to answer some of the following questions: -What is the importance of moral and behavioral dimension in the resistance of Prince Abdul Qadir? - How could Prince Abdelkaderestablish a modern Algerian state: Was this done thanks to his patriotism, or was it thanks to his humanitarian positions? -Then what is the reference on which Prince Abdul Qadir was based in his dealings with the French? -Then what is the approach of Prince Abdul Qadir and his soldiers in dealing with the French prisoners? -What is the extent of moral and behavioral presence in his literature, especially in his dealings with the French in particular, and other people of boredom (Christians in general)?